2020
DOI: 10.1177/0020764020952116
|View full text |Cite
|
Sign up to set email alerts
|

Psychological responses and lifestyle changes among pregnant women with respect to the early stages of COVID-19 pandemic

Abstract: Objectives: The COVID-19 pandemic has caused a profound impact on health and well-being of populations. However, there are limited studies that have investigated the psychological aspects of vulnerable groups including pregnant women amid the COVID-19 pandemic. Therefore, we aimed to assess the psychological impact of the COVID-19 pandemic among Chinese pregnant women from February 2020 until March 2020. Methods: Our study was conducted using a modified validated online questionnaire comprising of sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 16 publications
11
81
3
3
Order By: Relevance
“…The mean stress score of 126 pregnant women was 8.50 ± 5.06 ( Gu et al, 2020 ). In a study of the psychological reactions among pregnant women to the early stages of the COVID-19 pandemic, most of pregnant women reported increased financial stress (69.3 %), work stress (62.9 %), and home stress (59.6 %) ( Zhang and Ma, 2020 ). Besides, a descriptive-analytical cross-sectional study reported mild stress symptoms (16/205, 7.8 %), moderate stress symptoms (32/205, 15.6 %), and high stress symptoms (16/205, 7.6 %), extremely severe stress symptoms (3/205, 1.5 %), and the mean (standard deviation,SD) score of stress was 6.22 (4.25) ( Effati-Daryani et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean stress score of 126 pregnant women was 8.50 ± 5.06 ( Gu et al, 2020 ). In a study of the psychological reactions among pregnant women to the early stages of the COVID-19 pandemic, most of pregnant women reported increased financial stress (69.3 %), work stress (62.9 %), and home stress (59.6 %) ( Zhang and Ma, 2020 ). Besides, a descriptive-analytical cross-sectional study reported mild stress symptoms (16/205, 7.8 %), moderate stress symptoms (32/205, 15.6 %), and high stress symptoms (16/205, 7.6 %), extremely severe stress symptoms (3/205, 1.5 %), and the mean (standard deviation,SD) score of stress was 6.22 (4.25) ( Effati-Daryani et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 studies (Ayaz et al, 2020;Berthelot et al, 2020;Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;Gu et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;Sade et al, 2020;Silverman et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zanardo et al, 2020;Zhang and Ma, 2020) performed with 20 569 participants (16,797 pregnant women and 3,772 postpartum women) during the COVID-19 pandemic and with 3,677 pregnant women before the COVID-19 pandemic were included in this systematic review and metaanalysis. A total of 19 studies (Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…A total of 19 studies (Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;Sade et al, 2020;Silverman et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zhang and Ma, 2020) were cross-sectional, and 4 (Ayaz et al, 2020;Berthelot et al, 2020;Gu et al, 2020;Zanardo et al, 2020) were case-control studies. Among the 23 studies, 7 were located in China (Gu et al, 2020;He et al, 2020;Li et al, 2020;Liu et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zhang and Ma, 2020), 3 were implemented in America (Farewell et al, 2020;Preis et al, 2020;Silverman et al, 2020), 3 were performed in Turkey (Ayaz et al, 2020;Durankuş and Aksu, 2020;Oskovi-Kaplan et al, 2020), 3 were undertaken in Italy (Mappa et al, 2020;Saccone et al, 2020;…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations